A multicenter cross-sectional survey of the knowledge, attitude, and behaviour of nurses regarding dysphagia after anterior cervical spine surgery: a prospective multicentre study - Chen Yu; Luo Chunmei; Song Caiping (BMC, 2024)
Abstract Background The incidence of dysphagia after anterior cervical spine surgery is high, which directly affects the quality of life of patients after surgery. The knowledge, attitude, and behavior of nurses can affect the identification and management of patients after anterior cervical spine surgery. Therefore, we need a survey to understand the current status of nurses' knowledge, attitude, and behavior towards dysphagia after anterior cervical spine surgery. Objective To investigate the knowledge, attitude, and behaviour of orthopaedic nurses towards patients with dysphagia after anterior cervical spine surgery and provide recommendations for management and intervention. Method An online cross-sectional survey was conducted between March and June 2023, which among 894 orthopaedic nurses from 36 tertiary hospitals in Chongqing using a questionnaire. The questionnaire included general information and knowledge, attitudes, and behaviours related to the management of dysphagia after anterior cervical surgery. Results The orthopaedic nurses' mean score for dysphagia-related knowledge was 16.1 ± 3.640 (out of a total score of 30). The orthopaedic nurses' mean score for dysphagia-related attitude was 32.5 ± 4.623 (out of a total score of 40). The orthopaedic nurses' mean score for dysphagia-related behaviour was 43.6 ± 11.513 (out of a total score of 60). The results of statistical analysis showed that the dysphagia after anterior cervical spine surgery -related knowledge scores differed significantly among the nurses according to, education level, and training (P < 0.05). Correlation analysis showed that there was a positive correlation between the knowledge, attitude, and behaviour scores of neurological nurses and swallowing disorders after anterior cervical surgery (P < 0.05). Conclusion Targeted knowledge and skills training should be carried out to improve the rules and regulations for dysphagia after anterior cervical spine surgery. Multidisciplinary team cooperation is needed, and dietary service processes and management standards should be improved to improve the management ability of orthopaedic nurses for dysphagia after anterior cervical spine surgery.